Analisis Tingkat Kepuasan Masyarakat Terhadap Manajemen Pelayanan Publik Pada Kantor Lembang Sa’tandung Tana Toraja - Juprianto Tandi Belopa; Dina Ramba; Rati Pundissing (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2023)
. This research aims to determine the level of public satisfaction with public services at the Sa'tandung Lembang Office, Saluputti District, Tana Toraja Regency. This type of research is quantitative descriptive research. The data collection techniques used in this research were interviews, observation, documentation and questionnaires. The data analysis technique uses analysis and interpretation of the Community Satisfaction Survey (SKM). The results of research and discussion regarding the level of public satisfaction with public services at the Sa'tandung Lembang Office, Saluputti District, Tana Toraja Regency based on PermenPAN-RB number 14 of 2017 are seen from the 9 elements that have been implemented, so the SKM value obtained after conversion is a service SKM unit of 87 .75 service quality B which means Good. Based on indicators of public satisfaction with public services at the Sa'tandung Lembang Office, the SKM element was obtained whose highest value was cost reasonableness = 4 with a conversion value of 100, very good performance, and the lowest element was completion. time = 3.31, conversion value 82.75, good performance.